Acquisition of clofazimine resistance following bedaquiline treatment for multidrug-resistant tuberculosis. (January 2021) - Liu, Yuhong; Gao, Jingtao; Du, Jian; Shu, Wei; Wang, Lu; Wang, Yufeng; Xue, Zhongtan; Li, Liang; Xu, Shaofa; Pang, Yu
Highlights: The high rate of CFZ resistance among MDR-TB patients in China. Patients treated with BDQ-containing regimens achieve comparative culture conversion rate regardless of baseline CFZ susceptibility. The presence of acquired CFZ-resistance following BDQ treatment without known mutation indicates that other mechanisms conferring cross resistance to these two compounds may exist, and the whole genome sequencing analyses of the two isolates will be necessary to determine these novel mechanisms. Abstract: Objectives: We described the prevalence of clofazimine (CFZ) resistance in a multidrug-resistant tuberculosis (MDR-TB) cohort in China. We also aimed to identify dynamic changes in CFZ susceptibility and its molecular mechanism after exposure to bedaquiline (BDQ) and/or CFZ. Methods: The experimental settings were conducted based on our MDR-TB cohort receiving BDQ-containing regimens. Sequential isolates were obtained from patients. CFZ and BDQ susceptibility of isolates were determined using the minimum inhibitory concentration (MIC) method. The fragments of Rv0678 and pepQ were sequenced. Results: A total of 277 patients infected with MDR-TB were included in our study. CFZ resistance was noted in 23 (23/277, 8.3%) isolates. The rate of acquired CFZ resistance (12/189, 6.3%) was significantly greater than that of primary resistance (11/88, 12.5%, P = 0.028). Out of 23 CFZ-resistant isolates, five (5/23) were BDQ-resistant, and the other 18 (18/23) were susceptible to BDQ. Of note, nine 9/23) out of 23 CFZ-resistant isolates had mutations within either target genes. Kaplan-Meier analysis demonstrated that the baseline CFZ resistance had no influence on time to culture conversion in our cohort ( P = 0.828). Acquired CFZ resistance emerged in eight (8/94, 8.5%) patients during treatment for MDR-TB, including three patients receiving regimens without CFZ. Conclusions: Our results demonstrate the high rate of CFZ resistance among MDR-TB patients in China. Patients treated with BDQ-containing regimens achieve comparative culture conversion rate regardless of baseline CFZ susceptibility. The presence of acquired CFZ-resistance following BDQ treatment without known mutation indicates that other mechanisms conferring cross resistance to these two compounds may exist.